Development and Evaluation of Chewable Tablets of Calcium and Vitamin D - Sharma, Satish Kumar; Singh, Anand; Bhandari, Anil; Singh, Sudhir; Singh, Sumer (Asian Journal of Pharmaceutical Research and Development, 2020)
The aim of research work was to prepare a formulation of calcium and vitamin D chewable tablets by wet granulation method using excipients and to evaluate the tablet properties. In this research work vitamin D3 was used as vitamin D. The blend was compressed on a rotary compresson machine. Tablets were subjected to various tests (weight variation, thickness, hardness and assay of calcium and vitamin D3 etc) and the results were in compliance with the pharmacopoeial specifications. All physical properties studied indicate that all excipients are good pharmaceutical excipients for tablets. The aim of this work was to minimise the complexity of formulation and to make cost effective product. Since tablets to be prepared are chewable so sweetening and flavouring agents are to be incorporated to make the tablet palatable and easily acceptable.